2022
DOI: 10.1002/14651858.cd011535.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic pharmacological treatments for chronic plaque psoriasis: a network meta-analysis

Abstract: Systemic pharmacological treatments for chronic plaque psoriasis: a network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 627 publications
0
18
0
2
Order By: Relevance
“…49 A recent network meta-analysis of 167 studies reported the proportion of patients with psoriasis that reached 90% improvement on psoriasis area and severity index (PASI90) during the induction phase (8-24 weeks after randomisation) of various systemic treatments compared with controls. 25 Of all the anti-TNFs assessed, infliximab was found to have the highest probability of leading to PASI90 relative to placebo (RR: 50.19), followed by adalimumab (RR: 17.35), certolizumab pegol (RR: 13.30), and etanercept (RR: 10.65). 25 Another meta-analysis reported the efficacy of anti-TNFs with longerterm treatment, the number needed to treat to achieve PASI90 at 48 or 52 weeks was reported as adalimumab (2.17) certolizumab pegol (1.72), and etanercept (3.20).…”
Section: Psoriasismentioning
confidence: 95%
See 1 more Smart Citation
“…49 A recent network meta-analysis of 167 studies reported the proportion of patients with psoriasis that reached 90% improvement on psoriasis area and severity index (PASI90) during the induction phase (8-24 weeks after randomisation) of various systemic treatments compared with controls. 25 Of all the anti-TNFs assessed, infliximab was found to have the highest probability of leading to PASI90 relative to placebo (RR: 50.19), followed by adalimumab (RR: 17.35), certolizumab pegol (RR: 13.30), and etanercept (RR: 10.65). 25 Another meta-analysis reported the efficacy of anti-TNFs with longerterm treatment, the number needed to treat to achieve PASI90 at 48 or 52 weeks was reported as adalimumab (2.17) certolizumab pegol (1.72), and etanercept (3.20).…”
Section: Psoriasismentioning
confidence: 95%
“…25 Of all the anti-TNFs assessed, infliximab was found to have the highest probability of leading to PASI90 relative to placebo (RR: 50.19), followed by adalimumab (RR: 17.35), certolizumab pegol (RR: 13.30), and etanercept (RR: 10.65). 25 Another meta-analysis reported the efficacy of anti-TNFs with longerterm treatment, the number needed to treat to achieve PASI90 at 48 or 52 weeks was reported as adalimumab (2.17) certolizumab pegol (1.72), and etanercept (3.20). 50 Adalimumab and etanercept are also approved for use in paediatric patients with psoriasis.…”
Section: Psoriasismentioning
confidence: 95%
“…Treatments were ranked from the most to least efficacious according to SUCRA: infliximab (risk ratio (RR) 50.19, 95% confidence interval (CI) 20.92 to 120.45), bimekizumab (RR 30.27, 95% CI 25.45 to 36.01), ixekizumab (RR 30.19, 95% CI 25.38 to 35.93), and risankizumab (RR 28.75, 95% CI 24.03 to 34.39 In addition, infliximab, all four IL-17 inhibitors, risankizumab, and guselkumab achieved a higher PASI90 than ustekinumab, etanercept, adalimumab, and certolizumab. 23 …”
Section: Advantages/disadvantagesmentioning
confidence: 99%
“…L’outcome primario, PASI 90, è stato valutato a 12 settimane per la fase di induzione, così come quello secondario, PASI 75, che ancora oggi rappresenta l’indicatore da raggiungere per definire una terapia efficace, come riportato nelle Linee Guida della psoriasi della regione Emilia-Romagna ( 12 ). Entrambi gli outcome sono stati esplorati nell’analisi di scenario a 52 settimane per la fase di induzione e mantenimento, assumendo per quest’ultima la stessa efficacia della fase di induzione riportata nella network meta-analisi (NMA) Cochrane di Sbidian et al ( 15 ). Tale assunzione, validata da un panel di esperti, anche se non supportata da dati di comparazione indiretta, è in linea con i dati di efficacia clinica a 52 settimane del metotrexato e dei farmaci biologici riportati rispettivamente in Reich et al ( 16 ) e Leonardi et al ( 17 ).…”
Section: Metodiunclassified
“…L’efficacia delle terapie considerate in questo studio per il trattamento della PsO moderata-grave è stata valutata a 8-24 settimane, sulla base della stima del rischio relativo (RR) di ciascun trattamento versus placebo di raggiungere il PASI 90 e il PASI 75 riportato nella network meta-analisi (NMA) Cochrane di Sbidian et al ( 15 ) ( Tab. IV ).…”
Section: Metodiunclassified